Persuasive Communication Content Analysis To Create Impulse Buying During Live Shopee: Local Business Perspectives - Natalia Sari Pujiastuti; Sinta Pramucitra; Tika Ristia Djaya (Jurnal Indonesia Sosial Teknologi, 2023)
This research aims to analyse the persuasive communication content utilised by local entrepreneurs to generate impulse buying during Shopee Live sessions. Involving the perspective of local business operators, the study will identify the most effective persuasive communication strategies in prompting consumers to make impulsive purchases, particularly within e-commerce platforms like Shopee. By comprehending the dynamics of persuasive communication, this research can offer valuable insights to local entrepreneurs in enhancing the allure and effectiveness of their sales campaigns during Shopee Live sessions, thereby maximising sales potential and sustaining their businesses.